Ultrasonography of Parasitic Diseases in Domestic Animals: A Systematic Review - Andrea Corda; Francesca Corda; Valentina Secchi; Plamena Pentcheva; Claudia Tamponi; Laura Tilocca; Antonio Varcasia; Antonio Scala (Animals, 2022)
The aim of this review was to summarize the current knowledge on the application of ultrasonography in diagnosis, staging and monitoring of helminthic diseases in domestic animals. Only peer reviewed papers written in English language were included in this systematic review. All papers concerning unicellular parasites, wild animals, non-domestic experimental animals, or ex vivo or in vitro applications of ultrasonography were excluded from the review. A total of 122 papers met the inclusion criteria. Among them 47% concerned nematodes, 37% cestodes, and 16% trematodes with the genus Dirofilaria, Echinococcus, and Fasciola the most represented, respectively. Helminths can be recognized in ultrasound images by their morphology, size, and location. In some cases, the parasite stages are not directly seen by ultrasound, but the lesions caused by them can be easily visualized. Ultrasound imaging is taking on an increasingly important role in the diagnosis, staging, monitoring, and control of parasitic diseases in veterinary medicine. However, it cannot replace the clinical approach and the diagnostic tests commonly used in veterinary parasitology.